Effect of equine chorionic gonadotropin on pregnancy rate in Brown Swiss cows under high altitude conditions. Issue 1 (1st January 2020) - Mínguez, C.; Calvo, A.
ABSTRACT: The objective of the present study was to evaluate the administration of Equine Chorionic Gonadotropin (eCG) in a protocol of fixed-time artificial insemination (FTAI) to increase the pregnancy rate in cows subjected to high altitude conditions. These conditions could generate a syndrome of right-sided heart failure and, as consequence, animals trend to have a low body score condition with a decrease in fertility. The research was conducted with 84 lactating cows (Brown Swiss) randomly into two groups with a body condition score between 2.5 and 3.5, allocated at 3100 m above sea level. In the FTAI protocol, 400 IU of eCG was administered ( n  = 42) or not ( n  = 42) at progesterone intravaginal device removal. A significant improvement in pregnancy rate was found with eCG treatment in those cows with low body condition score (BCS of 2.5, scale 1–5), while no effect was found in those cows with higher BCS (i.e. 3.0 and 3.5). In conclusion, the addition of 400 IU of eCG in an FTAI in cows under high altitude conditions and low body conditions can improve the fertility.